Antimicrobial, antioxidant, and angiogenic bioactive silver nanoparticles produced using Murraya paniculata (L.) jack leaves. (1st February 2022) - Rama, Purushothaman; Baldelli, Alberto; Vignesh, Anandhan; Altemimi, Ammar B; Lakshmanan, Govindan; Selvam, Rajendran; Arunagirinathan, Narasingam; Murugesan, Kandasamy; Pratap-Singh, Anubhav
Murraya paniculata (MP) can be used as a reducing agent to produce silver nanoparticles (AgNPs) using a simple procedure. AgNPs are characterized in morphological and chemical properties, antioxidant activity, and cytotoxicity. The morphology of AgNPs derived from MP shows a face-centered cubic structure, spherical shape with an average particle size of 23 nm. The chemical structure shows characteristic peaks of AgNPs using UV-vis spectrometer at 438 nm. The formation of AgNPs is confirmed by analyzing their vibrational states under infrared radiation; typical peaks of AgNPs are recognized: at 3429 cm −1 (O-H stretch, H-bonded alcohols, phenols groups), 2923 cm −1 (C-H stretch alkanes), 1626 cm −1 (N-H bend 1° amines), 1583 cm −1 (C-C stretch in ring aromatic), 1039 cm −1 (C-N stretch aliphatic amines), 728 cm −1 (C-Cl stretch alkyl halides), and 589 cm −1 (C-Br stretch alkyl halides), respectively. AgNPs produced from MP show antioxidant activity and cytotoxicity. They show the highest sensitivity toward Bacillus cereus . Cytotoxicity of biosynthesized AgNPs, determined by scratch wound assay on in vitro human endothelial vein cell, created from MP showed dose-dependent activity. These AgNPs, at a concentration of 15.625 μg/mL, stimulate the proliferation and migration of endothelial cells (EC) showing an angiogenic activity.